An admissible estimator for the r th power of a bounded scale-parameter in a subclass of the exponential family under entropy loss function - Alikhani, S.; Mahmoudi, E.; Torabi, H. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider an admissible estimator for the rth power of a scale parameter that is lower or upper bounded in a subclass of the scale-parameter exponential family under entropy loss function. An admissible estimator of a bounded parameter in the family of transformed chi-square distributions is also given.